Path of Great Length: Toward the Formation of a Political Project for a Latin American Erotics of Liberation - Díaz Guzmán, Diana Alejandra (2023)
The present text is an original proposal within the erotic and political field of the Philosophy of Liberation. It is important to notethat this idea has been developed slowly and carefully, and it is still far from being finalized; thus, it remains a path of long and ongoing exploration. The proposal seeks to situate issues of gender and eroticism within the Ethics of Liberation (whose approach isnormative and is based on three principles), in order to guide praxis not only in denouncing the material, formal, and factual violation of alterity by patriarchy (understood as the historical experience of male hegemony), but also to provide clear orientations for human actions aimed at justice and goodness in the construction of a new systemic order, from which institutional frameworks and the cultural sphere ultimately emerge. It should also be noted that the three ethical-political principles of Liberation (Materiality, Formality, and Feasibility) are here analogized to the erotic field and are thus proposed from my perspective through an analectical interpretation.